PREFERENSI WISATAWAN NUSANTARA DI KAWASAN OBYEK WISATA ALAM KALIURANG DAERAH ISTIMEWA YOGYAKARTA - , ARDIYAN MAULANA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Kinahrejo and Tlogo Muncar are some of a few nature tourism objects that are well known to local tourist. Although located in the same area, these tourism objects retain different number of visitors. This research aims to understand the characteristic of domestic tourist (socio-demographically and phsycographically)